Moderating Effects of the Ego-Energy in Relation to Stress, Drinking Motives, and Depression in Korean Adult Males - Yoon, Doohah; An, Hyonggin (Frontiers in Psychology, 2021)
Although there have been numerous studies using stress and coping theories to explain the relationship between stress, drinking motives, and depression, few of them have attempted to verify these theories against adult male data. There is also a shortage of Korean studies, both theoretical and empirical, on the role of ego-energy as a moderating variable in the relationship between stress, drinking motives, and depression. This study uses a multiple-group analysis to investigate the moderating effects of the ego-energy on the aforementioned relationship in adult males. A transactional analysis tool showing the total amount of ego-energy called Ego-gram is used in this study. The tool reflects personality traits based on ego-energy state structural and functional analyses. The researchers collected empirical data to test the research model by conducting an online survey of adult males aged 20–50, residing in seven metropolitan cities and in the Gyeonggi Province. The survey yielded 567 samples. The data were then analyzed through structural equation modeling to understand the relationship between various factors. The results showed that, first, stress was positively correlated with drinking motives. Second, drinking motives had some influence on depression. Third, stress, drinking motives, and depression had statistically significant relationships between low-ego-energy and high-ego-energy groups. Overall, this study found a difference between the two ego-energy groups concerning the relationship between stress, drinking motives, and depression. Based on these results, practical implications were discussed as to how to strengthen the ego-energy, while also presenting future research directions to shed light on the precise mechanism of depression. This study is significant for exploring ways in which adult males cope with and prevent stress and depression, while also offering the basic data for improving the mental and physical health of adult males. This study is also significant for drawing attention to the necessity of developing various health and wellness programs adapted to the needs of this specific population segment while providing the data that may serve as the basis for developing such programs.